The effect of burning on saw trauma characteristics in bone - Maharaj, Zaineta (Department of Pathology, 2025)
Dismemberment and burning of a corpse are means recurrently used by criminals to facilitate the concealment of a homicide. Readily available dismemberment tools, such as saws, leave characteristic markings on bone that can be analysed by forensic tool mark analysists to estimate the class of weapon utilised in a case. As bone is vulnerable to morphological changes under high heat exposure, the burning process may alter and distort these marks, misleading the tool mark analysis. This study aimed to analyse and compare the characteristics of saw cut marks in bone before and after burning at various temperatures. Fifteen Ovis aries femora were used as an analogue for human long bones, and were traumatised with a hand saw, creating false start, incomplete, and complete cuts. Five femurs per temperature group were subjected to burning at 400 °C, 600 °C, and 800 °C for 30 minutes in a muffle furnace. Prevalence and metrics of saw cut mark characteristics were analysed pre- and postincineration using visual inspection, stereomicroscopy and silicon casting. Heat-induced alterations to saw mark characteristics included increases in kerf width and decreases in kerf depth, as well as visual enhancement of certain traits. The detection of exit chipping, regular striae, pull-out striae, and tooth hop striae improved post-incineration, even at high heatintensities. These results indicate most saw mark traits persist after burning, but that forensic tool mark analysts must consider the vulnerability of heat-induced metric alterations to these traits in their analyses. Further research is necessary on the effect of burning duration to heatinduced saw mark alterations on bone burned at various temperatures.